Real Hypersurfaces in Complex Two-Plane Grassmannians with Generalized Tanaka-Webster Invariant Shape Operator - Jeong, I.; Pak, E.; Suh, Y.J. (Журнал математической физики, анализа, геометрии, 2013)
In this paper, we introduce a new notion of the generalized Tanaka-Webster invariant for a hypersurface M in G₂(C^m+2), and give a non-existence theorem for Hopf hypersurfaces in G₂(C^m+2) with generalized Tanaka-Webster invariant shape operator. Введено новое определение обобщенного инварианта Танаки-Вебстера для гиперповерхности M в G₂(C^m+2) и доказана теорема о несуществовании гиперповерхностей Хопфа в G₂(C^m+2) с обобщенным инвариантным оператором в смысле Танаки-Вебстера.